2020
DOI: 10.1111/1467-8462.12383
|View full text |Cite
|
Sign up to set email alerts
|

The Cost of Coronavirus Uncertainty: The High Returns to Clear Policy Plans

Abstract: Policymakers face an extremely uncertain environment during COVID-19. Using a nonlinear VAR estimate for the Euro Area, we argue that the benefit of reducing policy uncertainty at a time dominated by pessimistic expectations amounts to several points of GDP. The impact on the economy of uncertainty shocks is much larger during periods of negative outlook for the future. We estimate the impact on industrial production of the current COVID-19 induced uncertainty to peak at a year-over-year growth loss of −15.4 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The pandemic risk was perceived differently for the short and long run. In a similar study, Pellegrino et al (12) investigated the benefit of reducing policy uncertainty on GDP using a nonlinear VAR estimation for the Euro Area. The authors showed that the impact of the pandemic on the economy of uncertainty shocks is much higher during periods of a negative outlook for the future.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The pandemic risk was perceived differently for the short and long run. In a similar study, Pellegrino et al (12) investigated the benefit of reducing policy uncertainty on GDP using a nonlinear VAR estimation for the Euro Area. The authors showed that the impact of the pandemic on the economy of uncertainty shocks is much higher during periods of a negative outlook for the future.…”
Section: Literature Reviewmentioning
confidence: 99%